2013
DOI: 10.1159/000350444
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Meiotic Recombination in Cattle <b><i>(Bos taurus)</i></b> and Three Wildebeest Species <b><i>(Connochaetes gnou, C. taurinus taurinus</i></b> and <b><i>C. t. albojubatus)</i></b>

Abstract: The karyotypic evolution in the family Bovidae is based on centric fusions of ancestral acrocentric chromosomes. Here, the frequency and distribution of meiotic recombination was analyzed in pachytene spermatocytes from Bos taurus (2n = 60) and 3 wildebeest species (Connochaetes gnou, C. taurinus taurinus and C. t. albojubatus) (2n = 58) using immunofluorescence and fluorescence in situ hybridization. Significant differences in mean numbers of recombination events per cell were observed between B. taurus and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 25 publications
3
18
0
Order By: Relevance
“…Interestingly, the recombination rates on the SCs of ovine metacentric chromosomes were reduced despite their higher relative length (30.27% of the total length of all SCs in the cell) compared to the orthologous acrocentrics in cattle and goats (28.94 and 27.88% of the total SC length, respectively). The observed reduction of the recombination in the metacentric chromosomes in sheep was not caused by a loss of genetic material in fused chromosomes as previously proposed in other bovids [Vozdova et al, 2013], because no significant differences were found in the relative mitotic lengths of sheep metacentric chromosomes compared with their acrocentric orthologs in cattle. Also, the bovine, ovine and goat genomic libraries available at the NCBI database show similar whole genome sizes, as well as the sizes of the individual chromosomes focused upon in this study ( table 3 ).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Interestingly, the recombination rates on the SCs of ovine metacentric chromosomes were reduced despite their higher relative length (30.27% of the total length of all SCs in the cell) compared to the orthologous acrocentrics in cattle and goats (28.94 and 27.88% of the total SC length, respectively). The observed reduction of the recombination in the metacentric chromosomes in sheep was not caused by a loss of genetic material in fused chromosomes as previously proposed in other bovids [Vozdova et al, 2013], because no significant differences were found in the relative mitotic lengths of sheep metacentric chromosomes compared with their acrocentric orthologs in cattle. Also, the bovine, ovine and goat genomic libraries available at the NCBI database show similar whole genome sizes, as well as the sizes of the individual chromosomes focused upon in this study ( table 3 ).…”
Section: Discussionsupporting
confidence: 85%
“…Despite the same number of autosomal arms in all studied species (FNa = 58), the observed recombination rate in sheep was higher than in the other 3 related species. This is even more surprising when we realize that the sheep genome contains 3 Robertsonian fusions (2n = 54) which are supposed to be responsible for a reduction of recombination on fused chromosomes [Dumas and Britton-Davidian, 2002;Merico et al, 2013;Vozdova et al, 2013;Capilla et al, 2014]. The increased recombination rates in sheep (33.1% above the mean in cattle) were associated with only a minor elevation of the total autosomal SC length (7.5%) which resulted in higher recombination density in sheep (0.244 ± 0.021) being one of the highest reported so far [Borodin et al, 2007;Segura et al, 2013].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies [Dutrillaux, 1986] reported a correlation between the number of chiasmata and the haploid number of chromosome arms followed by subsequent studies in a wide range of mammalian species [Pardo-Manuel de Villena and Sapienza, 2001;Segura et al, 2013]. In this context, substantial progress has been made in elucidating the mechanisms that control both the formation and genome-wide distribution of COs. MLH1 recombination maps have been constructed for a wide variety of mammalian species, including humans and non-human primates [Sun et al, 2005;Codina-Pascual et al, 2006;Hassold et al, 2009;Garcia-Cruz et al, 2011;Gruhn et al, 2013Gruhn et al, , 2016Baier et al, 2014], rodents [Froenicke et al, 2002;Dumont and Payseur, 2011;Baier et al, 2014;Basheva et al, 2014;Capilla et al, 2014], pigs [Muñoz et al, 2012;Mary et al, 2014Mary et al, , 2016, bovids [Vozdova et al, 2013[Vozdova et al, , 2014Sebestova et al, 2016], and other eutherian groups such as afrotherian species, carnivorans, and insectivorans [Borodin et al, 2008;Segura et al, 2013;Muñoz-Fuentes et al, 2015].…”
Section: Variability At the Chromosomal Levelmentioning
confidence: 99%
“…However, meiotic recombination (crossover, CO) also represents an important source of genetic variability by formation of new combinations of maternal and paternal alleles. Studies using immunofluorescence detection of the MLH1 protein as a surrogate for COs have shown a great variation in the frequency and chromosomal distribution of COs among mammalian species [Froenicke et al, 2002;Sun et al, 2004;Basheva et al, 2008;Borodin et al, 2008Borodin et al, , 2009Dumont and Payseur, 2011;Yang et al, 2011;Segura et al, 2013;Vozdova et al, 2013;Al-Jaru et al, 2014;Mary et al, 2014;Fröhlich et al, 2015;Sebestova et al, 2016;RuizHerrera et al, 2017]. The reasons behind this variability have not yet been completely elucidated.…”
mentioning
confidence: 99%